ASSESSMENT OF INSECTICIDES RESISTANCE IN FIELD POPULATION OF BACTROCERA ZONATA (SAUNDERS) (DIPTERA: TEPHRITIDAE) - M. K. Nadeem; S. Ahmed; S. Nadeem; M. Ishfaq; M. Fiaz (Journal of Animal and Plant Sciences, 2014)
Insecticides resistance against fourteen field populations of Bactrocera zonata (Saunders) (Diptera: Tephritidae) from Chichawatni, District Sahiwal, Pakistan to six insecticides viz., trichlorfon, malathion (Organophosphates), bifenthrin, lambda-cyhalothrin (Pyrethorids) , methomyl (Carbamate) and spinosad (Microbial) was assessed by topical assay under laboratory conditions. In insecticides bioassay, trichlorfon was observed susceptible to high resistance level (1.01-fold to 41.13-fold), bifenthrin and malathion were found susceptible to moderate resistance level (1.00-fold to 14.27-fold and 1.00-fold to 20.37-fold), lambda-cyhalothrin and spinosad were showed susceptible to low resistance (1.00-fold to 9.57-fold and 1.20 -fold to 9.95-fold), while effect of methomyl were remained as susceptible to all the tested populations. From the results it is concluded that methomyl was remained susceptible to all the tested populations, while other five tested insecticides have developed the resistance against B. zonata populations, which required adopting new strategies to overcome resistance in this pest.
Keywords: Field populations; Bactrocera zonata; organophosphates; pyrethorids; microbial insecticide resistant; carbamate susceptible